Strategic Assistance for Strengthening the Capacity of Village-Owned Enterprises (BUMDes) in Musi Banyuasin District: Transformasi Kapasitas Kelembagaan BUMDes di Kabupaten Musi Banyuasin Melalui Pendampingan Intensif dan Kemitraan Bisnis - Jun Harbi; Muhammad Nizar; Irkhamiawan Ma’ruf; Rahmat Kurniawan; Elva Dwi Harmilia; Innike Abdillah Fahmi; Novi Apriani; Heripan Heripan; Rika Puspitasari MZ (Altifani Journal: International Journal of Community Engagement, 2025)
This community service initiative seeks to enhance the institutional capacity and professionalism of Village-Owned Enterprises (BUMDes) via a strategic methodology that includes initial assessment, interactive workshops, intense mentoring, and facilitation of business partnership execution. The activities were conducted in eight villages within Musi Banyuasin Regency, South Sumatra. The employed methodologies encompassed participative analyses of BUMDes profiles, training in the formulation of work plans and business ideas, and the enhancement of branding strategies. The findings indicated that all BUMDes successfully developed strategic documents, including firm profiles, collaboration proposals, and SWOT analyses. Five BUMDes have initiated preliminary collaborations with neighboring enterprises. The primary obstacles encountered consist of insufficient human resource capability, restricted technological utilization, and scant managerial expertise. This program enhances both technical and administrative capabilities while fostering the establishment of sustainable collaborative networks between villages and the corporate sector. Additional proposals encompass training in corporate digitization, mentoring in negotiation, and the establishment of a more flexible organizational structure. This program aims to serve as a prototype for village empowerment through strategic partnerships and enhanced institutional capacity, which may be replicated in other locations.